MDGs, Taxpayers and Aid Effectiveness - McDonnell, Ida (OECD Development Centre Policy Insights, 2005)
MDGs and new aid-effectiveness targets are an opprtunity for donors to explain what they do before growing scepticism erodes taxpayer support for aid